2006
DOI: 10.1590/s0102-05362006000300016
|View full text |Cite
|
Sign up to set email alerts
|

Growth and development of lettuce plants at high NH4+:NO3- ratios in the nutrient solution

Abstract: Lettuce plants, cv. Vera, were grown at five NH4+:NO3- ratios in the nutrient solution in a 0.15 m deep sand growing bed. A standard nutrient solution was used, with the composition of, in mmol L-1, 11.0 NO3-; 1.5 H2PO4-; 6.5 SO4--; 7.5 Ca++; 10.0 K+ and 1.5 Mg++, and, in mg L-1, 0.42 Mn; 0.26 Zn; 0.05 Cu; 0.50 B; 0.04 Mo, and 4.82 chelate Fe. Ammonium nitrate was used to supply NH4+ concentrations of 2.5; 5; 7.5 and 10 mmol L-1, reaching NH4+:NO3- ratios of 0:11 (T1); 2.5:13.5 (T2); 5:16 (T3); 7.5:18.5 (T4) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 12 publications
2
12
0
2
Order By: Relevance
“…Soilless cultivation of lettuce recently gained popularity in South Africa because of improved yield and quality (Maboko & Du Plooy, 2008). A review of the literature showed conflicting results regarding the recommended spacing for lettuce in a soilless cultivation system (Niederwieser, 2001; Andriolo et al, 2006). Understanding the crop response to plant density is crucial for maximizing lettuce yield.…”
Section: May 2009mentioning
confidence: 99%
“…Soilless cultivation of lettuce recently gained popularity in South Africa because of improved yield and quality (Maboko & Du Plooy, 2008). A review of the literature showed conflicting results regarding the recommended spacing for lettuce in a soilless cultivation system (Niederwieser, 2001; Andriolo et al, 2006). Understanding the crop response to plant density is crucial for maximizing lettuce yield.…”
Section: May 2009mentioning
confidence: 99%
“…Carbon, nitrogen and water uptakes rates are the key processes determining fresh yield of vegetables [5]. Improved water use efficiency (WUE) representsa key factor in increasing crop productivity under suchwater scarcity conditions [10], and improving NUE might help to limit use of N fertilizers and to preserve the environment and public health [14].…”
Section: Resultsmentioning
confidence: 99%
“…Besides, soilless systems have relatively small additional expense and save both fertilizers and water. Due to drain large amounts of residual nutrient solutions with high salinity for the environment has been the biggest problem for soilless plant cultivation, then recycling and reuse is a current trend of sustainable farming systems [5]. The N use efficiency for lettuce ( Lactuca sativa L. ) was researched by monitoring the concentration of NH 4 + , NO 3 − and gross-N in nutrient solution and NO 3 − on lettuce leaves under the conditions of different management modes of replacing the nutrient solution and initial pH values.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, recycling and reuse of solutions is a trend in searching for sustainable agricultural production systems (Andriolo et al, 2006). Brun et al (2001) reported recycling systems based on EC control, consisting of adding a water complement to the drainage to decrease the EC and a complement nutrient solution to obtain the desired EC.…”
Section: Electrical Conductivity Managementmentioning
confidence: 99%